Torbiel ślinianki podjęzykowej u 71 letniej pacjentki = Sublingual ranula in a 71-year-old patient - Janas-Naze, Anna; Chiżyński, Adam; Szczepkowska, Aleksandra; Osica, Piotr (Journal of Education, Health and Sport, 2016)
Janas-Naze Anna, Chiżyński Adam, Szczepkowska Aleksandra, Osica Piotr. Torbiel ślinianki podjęzykowej u 71 letniej pacjentki = Sublingual ranula in a 71-year-old patient. Journal of Education, Health and Sport. 2016;6(1):11-16. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.44384 http://ojs.ukw.edu.pl/index.php/johs/article/view/44384 http://pbn.nauka.gov.pl/works/688620 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.12.2015. Revised 25.12.2015. Accepted: 05.01.2016. Torbiel ślinianki podjęzykowej u 71 letniej pacjentki Sublingual ranula in a 71-year-old patient Anna Janas-Naze, Adam Chiżyński, Aleksandra Szczepkowska, Piotr Osica Zakład Chirurgii Stomatologicznej UM w Łodzi Kierownik: dr hab. n. med. prof. nadzw. Anna Janas-Naze Adres do korespondencji: Piotr Osica Zakład Chirurgii Stomatologicznej UM w Łodzi 92-213 Łódź, ul. Pomorska 251 e-mail: pioosica@interia.pl tel. 42 675 75 71 Praca finansowana przez Uniwersytet Medyczny w Łodzi w ramach działalności statutowej nr 503/2-163-01/503-21-001. Streszczenie W artykule opisano przypadek występowania, diagnostykę i leczenie torbieli ślinianki podjęzykowej u 71- letniej pacjentki. Hasła indeksowe: torbiel ślinianki podjęzykowej, ranula, leczenie chrurgiczne Summary The article describes a case of sublingual ranula, methods of diagnostic and treatment. Key words: sublingual ranula, ranula, surgical treatment.